Estrategia de Inoculación de factores estresores en comunidad terapéutica de atención en adicciones de Bucaramanga (2020)
The present research work was carried out with the aim of knowing the effectiveness of the intervention program in Stress Inoculation Training (SIT) of Meichenbaum, to control stress in patients of a therapeutic community in addictions to psychoactive substances (SPA) of Bucaramanga, in order to improve their learning and training process with this program. It is designed in a quantitative approach of descriptive type, with measures pre and post test, using as instrument the SISCO Inventory of the Academic Stress valid for Colombia (Jaimes & Malo, 2008); the main results indicate in the pre test an arithmetic average of 92. 96 points locating the results in a Medium high level of stress, contrasted with the average of the post-test results of 75.61 points finding a Low level of stress, in turn, the results of the statistical test T-student in this study, demonstrated the significant difference between the pre and post-test findings, being demonstrated the effectiveness of the program to control stress